Pemanfaatan Gadai Boat Dalam Pandangan Fiqh Muamalah - Nurhabni, Nurhabni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The people of Jawi-Jawi village in meeting the needs of living work as farmers, laborers and entrepreneurs, because of the many needs, some local people are looking for alternative ways to meet their needs by pawning their valuables, according to local habits, the goods that are pawned will be taken advantage of by the local community. pawnee. The purpose of this study was to determine the view of muamalah fiqh on the use of pawns.Pawn (rahn) is a category of debt-receivable agreements, and the practice of this pawn has existed since the time of the Prophet Muhammad, Pawn in fiqh mu'amalah is known as the word ar-rahn, which is storing an item as debt dependent.This type of research is field research, a descriptive approach, which aims to describe a situation and event based on the facts that occur in the field to obtain conclusions. The subjects in this study were rahin and murtahin who made use of pawn boats, then the data collection technique in this study was snowball sampling using interviews. To get the results of the study, the authors conducted interviews and observations to rahin and murtahin, religious leaders and the people of Jawi-jawi Village.The results of the study indicate that the pledge made by the Jawi-Jawi community in terms of the contract and its pillars has fulfilled what has been described in the muamalah fiqh study, but when viewed from the goods that are used as collateral, the murtahin uses it which causes deviations in the practice of pawning, it is a habit of the local community due to the lack of knowledge about how the collateral should be treated by rahin and murtahin parties.